2022
DOI: 10.3389/fimmu.2022.971189
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the use of exosomes for the treatment of ALI/ARDS

Abstract: Acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) is a critical clinical syndrome with high morbidity and mortality. Currently, the primary treatment for ALI/ARDS is mainly symptomatic therapy such as mechanical ventilation and fluid management. Due to the lack of effective treatment strategies, most ALI/ARDS patients face a poor prognosis. The discovery of exosomes has created a promising prospect for the treatment of ALI/ARDS. Exosomes can exert anti-inflammatory effects, inhibit apoptosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 150 publications
0
19
0
Order By: Relevance
“…In the context of ALI, exosomes have been a subject of significant research interest due to their potential impact on the pathogenesis and resolution of the condition 26 . Several preclinical studies in animal models of ALI have demonstrated the therapeutic potential of exosomes in mitigating lung injury and promoting recovery, suggesting that exosomes could be used as a novel approach for the treatment of ALI in the future 27,28 . Overall, the potential impact of exosomes on ALI reflects their role as key mediators of intercellular communication and their therapeutic potential in modulating inflammatory responses and promoting tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of ALI, exosomes have been a subject of significant research interest due to their potential impact on the pathogenesis and resolution of the condition 26 . Several preclinical studies in animal models of ALI have demonstrated the therapeutic potential of exosomes in mitigating lung injury and promoting recovery, suggesting that exosomes could be used as a novel approach for the treatment of ALI in the future 27,28 . Overall, the potential impact of exosomes on ALI reflects their role as key mediators of intercellular communication and their therapeutic potential in modulating inflammatory responses and promoting tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…In clinics, the primary treatment for ALI/ARDS mainly focuses on symptomatic therapy including mechanical ventilation and fluid management. However, due to the lack of effective therapeutic strategies, the prognosis for most ALI/ARDS patients is despondent (Liu et al 2022b ). The pathogenesis of ALI/ARDS has revealed inflammation plays a pivotal role (Mokrá 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Currently, there have no specific therapies for ALI/ARSD. [ 3 ] The progression of ALI is a series of biological cascade reactions characterized by processes such as alveolar epithelial cells injury, neutrophils infiltration, hyaline membranes formation, alveolar edema, inflammation, and eventually fibrosis. [ 4 ] During the progression of ALI, reactive oxygen species (ROS) generated by the lung itinerant and resident leukocytes, lung parenchymal cells, circulating oxidant‐generating enzymes, and inhaled oxygen are overproduced.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Currently, there have no specific therapies for ALI/ARSD. [3] The progression of ALI is a series of biological cascade reactions characterized by processes such as alveolar epithelial cells injury, neutrophils infiltration, hyaline membranes formation, the lung targeted accumulation. Nevertheless, the construction of ceria nanowires that are suitable for in vivo application has not yet been achieved because the previously synthesized ceria nanowires were too big in both diameter and length, [18] which could not be well stabilized in water or physiological solution.…”
Section: Introductionmentioning
confidence: 99%